Dynamic imaging of iel-iec co-cultures allows for quantification of cd103-dependent t cell migration - Enderle, Karin; Dinkel, Martin; Spath, Eva-Maria; Schmid, Benjamin; Zundler, Sebastian; Tripal, Philipp; Neurath, Markus; Hildner, Kai; Neufert, Clemens (International Journal of Molecular Sciences, 2021)
Intraepithelial lymphocytes (IEL) are widely distributed within the small intestinal epithelial cell (IEC) layer and represent one of the largest T cell pools of the body. While implicated in the pathogenesis of intestinal inflammation, detailed insight especially into the cellular cross-talk between IELs and IECs is largely missing in part due to lacking methodologies to monitor this interaction. To overcome this shortcoming, we employed and validated a murine IEL-IEC (organoids) ex vivo co-culture model system. Using livecell imaging we established a protocol to visualize and quantify the spatio-temporal migratory behavior of IELs within organoids over time. Applying this methodology, we found that IELs lacking CD103 (i.e., integrin alpha E, ITGAE) surface expression usually functioning as a retention receptor for IELs through binding to E-cadherin (CD324) expressing IECs displayed aberrant mobility and migration patterns. Specifically, CD103 deficiency affected the ability of IELs to migrate and reduced their speed during crawling within organoids. In summary, we report a new technology to monitor and quantitatively assess especially migratory characteristics of IELs communicating with IEC ex vivo. This approach is hence readily applicable to study the effects of targeted therapeutic interventions on IEL-IEC cross-talk.
CRIS-Team Scopus Importer:2021-05-21
Keywords: CD103; Intestinal organoids; Intraepithelial lymphocytes; Life cell imaging; Lympho-cyte migration